A discursive approach to the analysis of epistemic cognition. (March 2018) - Knight, Simon; Littleton, Karen
Abstract: A core concern in learning is coming to understand the ways in which claims of knowledge are made. The epistemic cognition literature typically characterises this learning in terms of how learners cognitively conceptualise the source and nature of knowledge. Recent work has offered alternative accounts of epistemic cognition that recognise the discursive nature of the construct. These accounts are derived from analysis of the ways that learners talk about knowledge in tasks such as evaluating scientific claims from sources of varying qualities. In this paper we draw on this recent work to advance a novel approach to the analysis of discourse data in epistemic contexts. This approach is exemplified through its application to an existing dataset, demonstrating both the application of the approach and the particular kinds of discourse that learners engaged in. This discursive approach has the potential for broad application in the learning sciences' treatment of epistemic cognition.